Adapting SLP to ad-hoc environment - Pietiäinen, Janne (2006)
Ad-hoc networking, where network structure is created dynamically as nodes enter and leave the network, has recently become an active reseach subject. As majority of existing network protocols has been targeted to be used in an environment, where a static network configuration and the option of using registry repositories is enabled, they need tailoring for ad-hoc networking. In this paper, we discuss how Service Location Protocol (SLP) can be modified for such a dynamic environment starting from the requirements of applications that are to be run, and user’s intentions. The adaptations we have implemented include passive service discovery where the amount of network traffic needed for service discovery can be reduced, security related features for improved privacy, gateway function that offers connectivity to external networks, and service discovery proxies that assist in the discovery of services between ad-hoc and fixed networks. The paper also addresses implementation of these features.